2005
DOI: 10.1620/tjem.207.325
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Family Composition Related to Discharge Destination and Length of Hospital Stay after Acute Stroke

Abstract: Informal care by family members still plays an important role in home care after acute stroke. This study determined the clinical and demographic factors, such as family structure, that predict discharge to home and length of hospital stay (LOS) after acute stroke hospitalization. We reviewed the sex, age, family structure before stroke, type of stroke, size of the lesion, activities of daily living (ADL) function at discharge, discharge destination, and LOS of stroke patients (114 cerebral infarctions and 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…(8) Interestingly, a study by Ohwaki et al found that women living with only their husband were associated with pLOS. (9) A recent study by Bo et al revealed associations between prolonged hospital stay and cognitive impairment, functional dependence and higher comorbidity burden. (10) Other studies have also evidenced that poorer functional status, (11) the presence of cognitive impairment and walking difficulties (12) are associated with pLOS.…”
Section: Introductionmentioning
confidence: 97%
“…(8) Interestingly, a study by Ohwaki et al found that women living with only their husband were associated with pLOS. (9) A recent study by Bo et al revealed associations between prolonged hospital stay and cognitive impairment, functional dependence and higher comorbidity burden. (10) Other studies have also evidenced that poorer functional status, (11) the presence of cognitive impairment and walking difficulties (12) are associated with pLOS.…”
Section: Introductionmentioning
confidence: 97%
“…Risk prediction models involving a number of selected variables have been established using multivariable regression models. [1][2][3][4][5][6] However, quantifying the risk for clinical practice directly from the multiple logistic regression models is difficult because of complicated calculation. For simplifying the computation, the Framingham Heart Study used Cox proportional hazards regression methods to estimate cardiovascular diseases risk using risk scores.…”
mentioning
confidence: 99%
“…Glader et al (19) explained that the reason of functional inadequacy of females at 3 months post-stroke was the more advanced age compared to males and more risk factors. However, Ohwaki et al (20) stated that there was no effect of gender on functional impairment in patients at 2 months post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although the functional status at admission in female patients was better, there was no difference between genders in terms of FIM gain and FIM efficiency. Nevertheless, there are conflicting results in the literature on gender and its effect on functional improvement (16)(17)(18)(19)(20)25,28). In a study by Hachisuka et al (16), it has been found that although there was no significant difference in terms of motor function in stroke between female and male patients, FIM scores of male patients with stroke tended to be lower than those of female patients with stroke.…”
Section: Discussionmentioning
confidence: 99%